Seasonal Influenza Vaccine Awareness and Factors Affecting Vaccination in Pakistani Society - Saleem Akhtar, Zainab Iqbal, Ammara Zafar, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Influenza, more commonly referred as “flu”, is a highly contagious viral infection of the nose, throat and lungs that impacts people of all ages and occurs in late fall, winter and early spring. Objectives: The main objective of the study is to find the seasonal influenza vaccine awareness and factors affecting vaccination in Pakistani society. Material and methods: This cross-sectional study was conducted in DHQ hospital, Bhakkar during 2021 to January 2022. The importance and purpose of the study was explained to the participants. After verbal consent, the patients was asked to answer simple questions which was read out from the performa prepared. Results: The data was collected from 100 patients. Mean age of the participants was 39.69± 15.86 years. Seven patients had herpes zoster infection. Four patients had influenza. Five patients had pneumonia. One had dengue fever. And one had herpes genitalis infection in recent five years. 59 (59.7%) of the patients were taking conventional disease-modifying antirheumatic drugs (DMARDs), and nine (9.8%) of the patients were using biological agents. Conclusion: It is concluded that knowledge, attitude and practice of participants showed satisfactory outcomes. Autoimmune diseases have a complex multifactorial etiology and many factors can contribute to their onset.